2012
DOI: 10.1007/s00418-012-1026-0
|View full text |Cite
|
Sign up to set email alerts
|

Localization of decorin gene expression in normal human breast tissue and in benign and malignant tumors of the human breast

Abstract: The small extracellular matrix proteoglycan decorin which possesses a potent antitumor activity has been shown to be present in various amounts in the stroma of several tumors including those of the breast. Regarding decorin in breast malignancies the published data are conflicting, i.e., whether breast cancer cells express it or not. Here, we first compared decorin gene expression levels between healthy human breast tissue and selected types of human breast cancer using GeneSapiens databank. Next, we localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…Recently, we have shown that different types of human breast cancer cells totally lack decorin mRNA [19]. We have also shown that the adhesion, proliferation and apoptosis of MCF-7 human breast cancer cells can be influenced by decorin transduction [19].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, we have shown that different types of human breast cancer cells totally lack decorin mRNA [19]. We have also shown that the adhesion, proliferation and apoptosis of MCF-7 human breast cancer cells can be influenced by decorin transduction [19].…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, delivery of decorin gene or protein has been demonstrated to lead to growth retardation of different cancers [16][18] through various mechanisms of action such as via binding to growth factor receptors mentioned above and modulating their activity [11]. Recently, we have shown that different types of human breast cancer cells totally lack decorin mRNA [19]. We have also shown that the adhesion, proliferation and apoptosis of MCF-7 human breast cancer cells can be influenced by decorin transduction [19].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular matrix macromolecules are involved in cellular physiologic events and pathological processes (43). Among these, Fmod and Dcn, extracellular matrix proteoglycans, have been designated as potent antitumor molecules and the lack of these proteins is permissive for tumorigenesis (44).…”
Section: Discussionmentioning
confidence: 99%
“…This protein is found in normal connective tissues, including the bone, where it binds to and cross-links collagen fibrils [14]. Decorin is also found in tumor ECM and is mainly attributed to surrounding, non-malignant stromal cells (tumor cells express little decorin) [1517]. However, decorin expression is decreased in stromal cells of many tumors compared to normal tissues and inversely correlates with prognosis of breast and lung carcinomas [16, 18, 19].…”
Section: Small Leucine-rich Proteoglycans (Slrps)mentioning
confidence: 99%